The RNA cargo in small extracellular vesicles from chicken eggs is bioactive in C57BL/6 J mice and human peripheral blood mononuclear cells ex vivo - Fratantonio, Deborah; Munir, Javaria; Shu, Jiang; Howard, Katherine; Baier, Scott R.; Cui, Juan; Zempleni, Janos (Frontiers in Nutrition, 2023)
Small extracellular vesicles (sEVs) and their RNA cargo in milk are bioavailable in humans, pigs, and mice, and their dietary depletion and supplementation elicits phenotypes. Little is known about the content and biological activity of sEVs in foods of animal origin other than milk. Here we tested the hypothesis that sEVs in chicken eggs (Gallus gallus) facilitate the transfer of RNA cargo from an avian species to humans and mice, and their dietary depletion elicits phenotypes. sEVs were purified from raw egg yolk by ultracentrifugation and authenticated by transmission electron microscopy, nano-tracking device, and immunoblots. The miRNA profile was assessed by RNA-sequencing. Bioavailability of these miRNAs in humans was assessed by egg feeding study in adults, and by culturing human peripheral blood mononuclear cells (PBMCs) with fluorophore-labeled egg sEVs ex vivo. To further assess bioavailability, fluorophore-labeled miRNAs, encapsulated in egg sEVs, were administered to C57BL/6 J mice by oral gavage. Phenotypes of sEV RNA cargo depletion were assessed by feeding egg sEV and RNA-defined diets to mice and using spatial learning and memory in the Barnes and water mazes as experimental readouts. Egg yolk contained 6.30 × 1010 ± 6.06 × 109 sEVs/mL, which harbored eighty-three distinct miRNAs. Human PBMCs internalized sEVs and their RNA cargo. Egg sEVs, loaded with fluorophore-labeled RNA and administered orally to mice, accumulated primarily in brain, intestine and lungs. Spatial learning and memory (SLM) was compromised in mice fed on egg sEV- and RNA-depleted diet compared to controls. Egg consumption elicited an increase of miRNAs in human plasma. We conclude that egg sEVs and their RNA cargo probably are bioavailable. The human study is registered as a clinical trial and accessible at https://www.isrctn.com/ISRCTN77867213.